2013
DOI: 10.1002/cne.23365
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and morphological characterization of cells in superficial layers of rat presubiculum

Abstract: The presubiculum (PrS) plays critical roles in spatial information processing and memory consolidation and has also been implicated in temporal lobe epileptogenesis. Despite its involvement in these processes, a basic structure-function analysis of PrS cells remains far from complete. To this end, we performed whole-cell recording and biocytin labeling of PrS neurons in layer (L)II and LIII to examine their electrophysiological and morphological properties. We characterized the cell types based on electrophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 44 publications
2
23
1
Order By: Relevance
“…In fact, these cells exhibited electrophysiological properties similar to those of pyramidal cells, but had a more depolarized RMP (bursting PC −64.6 ± 1.9 mV vs. regular PC −73.3 ± 0.4 mV, P < 0.001) in good agreement with previous reports (Simonnet et al 2013). In contrast to previous studies, however, we found these bursting neurons throughout all layers and not restricted to layer IV (Simonnet et al 2013) or superficial layers (Abbasi and Kumar 2013). …”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…In fact, these cells exhibited electrophysiological properties similar to those of pyramidal cells, but had a more depolarized RMP (bursting PC −64.6 ± 1.9 mV vs. regular PC −73.3 ± 0.4 mV, P < 0.001) in good agreement with previous reports (Simonnet et al 2013). In contrast to previous studies, however, we found these bursting neurons throughout all layers and not restricted to layer IV (Simonnet et al 2013) or superficial layers (Abbasi and Kumar 2013). …”
Section: Resultscontrasting
confidence: 99%
“…There is increasing knowledge about the diversity of cell types in the presubiculum (Abbasi and Kumar 2013; Simonnet et al 2013; Nassar et al 2015; Preston-Ferrer et al 2016), but little is known about its network topology. In the presubiculum, layers I to III are usually referred to as superficial layers and layers V and VI as deep layers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduced inhibitory synaptic drive noted in LII stellate cells under epileptic conditions (Kobayashi et al 2003;Kumar et al 2007;Tolner et al 2007) is consistent with diminution of PrS-mediated synaptic inhibition arising in part from either loss of GABAergic neurons in PrS, including MEA-targeting projection neurons (Drexel et al 2012;van Vliet et al 2004), loss of local GABAergic interneurons in MEA (Kumar and Buckmaster 2006;van Vliet et al 2004) and/or downregulation of GABA subunits mediating tonic inhibition (Drexel et al 2013). The loss of GABAergic neurons in PrS is substantiated by the absence of stuttering cells in epileptic rats (Abbasi and Kumar 2013;Abbasi and Kumar 2014 new synapses between target-deprived afferents from PrS and surviving LIII neurons (Scharfman et al 1998;Tolner et al 2005). Our data with focal application of glutamate in the PrS however did not indicate an increased PrS influence of surviving LIII pyramidal neurons in MEA.…”
Section: Discussionmentioning
confidence: 63%